FROM NETS TO NETWORKS: CAN DIGITAL TRANSFORMATION REVOLUTIONIZE THE FISHERIES SUPPLY CHAIN? - Christy Clayde Latupeirissa Latupeirissa; Hansen Rumtutuly; Paskanova Christi Gainau (Widya Mandala Surabaya Catholic University, 2026)
Research Purposes. This study aims to examine the effects of technological capability, organizational capacity, and environmental conditions on the performance of the fisheries supply chain in archipelagic regions, using the Technology–Organization–Environment (TOE) framework. Research Methods This research employs a quantitative approach, surveying 65 active fishermen from four coastal villages in Maluku and analyzing the data using multiple linear regression in SPSS version 27. Research Results and Findings. The findings reveal that technological capability and environmental support significantly and positively influence the performance of the fisheries supply chain. At the same time, organizational factors show no statistically significant effect, implying that strengthening digital infrastructure and supportive external environments is more critical than relying on internal organizational structures to enhance supply chain effectiveness in island and remote regions. Furthermore, the findings have a significant impact on improving operational efficiency, expanding market access, and enhancing financial transparency, thereby strengthening both supply chain effectiveness and data-driven decision-making within the fisheries sector.